La population, grande oubliée des politiques de prévention et de gestion territoriales des risques industriels : le cas de l’agglomération rouennaise - Justine Fenet; Éric Daudé (Cybergeo)
As part of the ESCAPE research program on mass evacuation strategies for population in crisis management, we carried out a survey in the Rouen agglomeration in 2018. This survey focused on knowledge of the warning signal and safety instructions in populations exposed to industrial risk during the day. The accident at the Lubrizol factory on September 26, 2019 gives acuity to certain results of this study which may shed light on the current debate on methods of alerting, transmitting safety instructions and protecting populations.More than 70% of those questioned do not know the national warning signal emitted by sirens and almost 60% do not know the instructions associated with it in the context of an industrial accident. This lack of knowledge would translate into a variety of reflex reactions in the event of an alert being triggered, ranging from indifference to flight, while awaiting additional information. Non-resident populations and tourists have the lowest levels of knowledge of industrial risk safety instructions. When they are known, the instructions are interpreted differently and followed according to the means of travel used by the people at the time of the survey. For the motorist, the abandonment of the vehicle raises many questions and encourages him to continue his journey or flee the area. For the pedestrian, finding shelter can be a real challenge in an urban environment. The vast majority of security personnel and facility managers we interviewed said that they would not allow people into their facility in the event of an alert. The following suggestions for improvement can thus be proposed: (i) a more regular preventive information policy which affects the entire population attending and not only residing in an area at industrial risk, (ii) multi-channel warning and communication means to inform the populations present in a danger zone and (iii) stronger involvement of establishments welcoming the public and their staff in keeping people safe. These three components are elements to be initiated or reinforced to reduce the exposure and vulnerability of populations faced with an industrial accident.